Framing of the 2008 Malaysian General Election Results by the English Language Press - Chai , Ming Hock; Adnan Hussein (Universiti Kebangsaan Malaysia, 2011)

(untitled)
Various observers heralded the 2008 Malaysian General Election as the ‘political tsunami’. The ruling coalition Barisan Nasional (BN) lost the symbolic two-third control of the Parliament. The Opposition collectively controls the state legislature of five states. In the past, general elections in Malaysia have become a predictable affair with the BN’s greater access to the media, money and governmental machinery. With the glowing pre-election coverage on the ruling coalition by the press, how then does the press make sense of the election result – devastating for the ruling coalition by Malaysian standard? How would the print media response and interpret such unexpected result? This article explores media framing of the results, factors and the meaning of it in Malaysian political landscape. This study is important because mass media plays an important role in setting frames of reference that readers use to interpret events or issues. This article explores the framing of the 2008 Malaysian General Election results by the English language press. Data collection focused on three Malaysian English language newspapers with analysis on the news and commentaries including news stories and features, editorials and letters to the editor, from the Election Day on 8th March to the formation of the new Malaysian Cabinet.